Idarubicin-intensified BUCY2 conditioning regimen improved survival in high-risk acute myeloid, but not lymphocytic leukemia patients undergoing allogeneic hematopoietic stem cell transplantation: A retrospective comparative study. (July 2016) - Fang, Jun; Zhang, Ran; Wang, Huafang; Hong, Mei; Wu, Qiuling; Nie, Dimin; You, Yong; Zhong, Zhaodong; Li, Weiming; Hu, Yu; Xia, Linghui
Highlights: We compared IDA-BUCY2 regimen for high-risk ALL versus AML undergoing allo-HSCT. IDA-BUCY2 regimen reduces relapse of high-risk AML undergoing allo-HSCT, but not ALL. IDA-BUCY2 regimen can improve survival of high-risk AML receiving allo-HSCT. Abstract: The intensity of conditioning regimen is highly correlated with outcomes of allogeneic hematopoietic stem cell transplantation (allo-HSCT). We have previously reported that idarubicin (IDA) intensified BUCY2 regimen could reduce relapse and improve survival for high-risk hematological malignancies undergoing allo-HSCT. However, there is no published study comparing the efficacy of IDA-BUCY2 regimen for high-risk acute myeloid leukemia (AML) versus acute lymphocytic leukemia (ALL). We further retrospectively compared therapeutic outcomes of intensified conditioning regimen on 140 high-risk AML and ALL patients in the data analyses. IDA 15 mg/m 2 /d was administered by continuous infusion from day −11 to −9, followed by intravenous injection of busulfan (BU) (3.2 mg/kg/d) from day −6 to −4, and intravenous injection of cyclophosphamide (CY) (1.8 g/m 2 /d) from day −3 to −2 in IDA-BUCY2 regimen. For high-risk AML, cumulative probabilities of 3-year relapse rates in IDA-BUCY2 and traditional BUCY2 regimens were 16.9%, 43.3% ( P = 0.016). Cumulative probabilities of 3-year overall survival (OS) and disease-free survival (DFS) were 69.2% vs 44.0% ( P = 0.024), and 66.9% vs 38.2% ( P = 0.01). However, two regimens showed no significant differences for high-risk ALL. Multivariate analysis also indicated that IDA intensified BUCY2 conditioning was the favorable variable to reduce relapse and elevate survival for high-risk AML patients. In conclusion, IDA-BUCY2 regimen reduces relapse and improves survival for high-risk AML undergoing allo-HSCT, but not presenting uniform therapeutic effects for high-risk ALL.